Design and Evaluation of an Augmented Reality Application for Learning Workshop Tool Recognition - Pramudita, Resa; Rohendi, Dedi; Pawinanto, Roer Eka; Rizqulloh, Muhammad Adli; Fauzan, Mochamad Rizal; Suryadi, Dedy; Kuntadi, Iwa (Universitas Pendidikan Indonesia (UPI), 2024)
This study aims to design and evaluate an Augmented Reality (AR) application for workshop tool recognition, with a focus on enhancing interactivity and student engagement in technical education. Developed using the ADDIE methodology—Analysis, Design, Development, Implementation, and Evaluation—the application integrates Blender for 3D modelling, Unity for development, and Vuforia for AR tracking. Usability was assessed through the System Usability Scale (SUS), involving 48 students from workshop practicum and Occupational Health and Safety (OHS) courses. The application achieved a SUS score of 50.5, classified as Fair according to the classification by Bangor et al. (2009). Key usability aspects were rated positively, including comfort (4.2), ease of use (4.0), functional integration (3.9), stability (4.1), and ease of learning (4.3). While the study highlights the application's potential as an effective learning tool, limitations include a small, institution-specific sample size. Future research should examine its adaptability in broader educational contexts and assess its impact on student learning outcomes. This study supports the integration of AR in technical education, fostering more interactive, efficient, and Industry 4.0-aligned learning environments.